Implementasi Corporate social responsibility Berbasis Kearifan Lokal: (Studi Pada LPD Desa Adat Kesiman Denpasar Timur) - Ni Komang Dani Suryani; I Wayan Sudiana; I Putu Deddy Samtika Putra (Jurnal Widya Akuntansi dan Keuangan, 2025)
The aim of this research is to find out what implementation of corporate social responsibility is based on local wisdom in the LPD of Kesiman Traditional Village. This research uses qualitative methods. Data analysis was carried out by the process of systematically searching and compiling research findings from the results of interviews, documentation and field data. The results of the research findings can be interpreted more deeply to find meaning so that conclusions can be drawn so that the research results can be understood. The results of the research can be stated that the implementation of the corporate social responsibility funds of the LPD of Kesiman Traditional Village is always based on the concept of local Balinese wisdom, especially the Tri Hita Karana philosophy, namely Parhyangan, Pawongan, and Palemahan in accordance with the awig-awig and pararem of the Kesiman Traditional Village which have been established, including the Parhyangan concept which is realized in the form of giving punia funds every 6 months at the Kahyangan Tiga Temple of Kesiman Traditional Villages, Dang Kahyangan Temple, and other temples in the Kesiman Traditional Village environment include construction, repair and preservation of temples, especially Pengerebongan Temple. The Pawongan concept is realized by providing compensation programs for the people of the Kesiman Traditional Village who pass away, implementing mass Ngaben, Memukur and Metatah programs for the people of the Kesiman Traditional Village which are carried out routinely every 5 (five) years. The Palemahan concept is realized with a program of providing rubbish bins to every banjar in the Kesiman Traditional Village environment, support for ogoh-ogoh competition activities, Pengerebongan penjor, Baleganjur, and coaching for the Kesiman Traditional Village community